Counterterrorism Diplomacy: ASEAN’s New Chapter of Regional Engagement - Frega Ferdinand Wenas Inkiriwang (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2024)
Counterterrorism has become a global trend since 9/11. Following the incident, the U.S. launched the Global War on Terror, which developed numerous international partnerships in dealing with terrorism. This included the Southeast Asia region. Most ASEAN countries have leveraged their cooperation through counterterrorism diplomacy ever since. This approach, however, endorsed the law enforcement agency due to the adopted criminal justice model. With the rise of the Islamic State (IS) movement, which links with various terrorist networks, the threat of terrorism has gained more attention in Southeast Asia, particularly after the Marawi incident. Complicatedly, the IS merged with separatist and terrorist groups in the South Philippines. Many observers predicted that if it is still uncontrollable, it may create a spillover to surrounding ASEAN countries. Thus, this circumstance has generated an opportunity for greater collaboration among ASEAN countries in dealing with ISIS in the region. Unlike past cooperation, this new chapter may facilitate a more substantial portion of military-to-military engagement. Counterterrorism diplomacy may potentially strengthen regional engagement, which has been restrained due to the South China Sea dispute with China.